Implementasi Media Pembelajaran Digital Berbasis Animaker Dalam Meningkatkan Motivasi Belajar Siswa - Tapatab, Shintya M.; Kollo, Fredik Lambertus (Jurnal Lazuardi, 2025)
Implementation of learning media as one of the efforts to prevent the problem of lack of motivation in learning. The purpose of this study is to determine the implementation of digital learning media based on Animeker in improving student learning motivation. The method used in this study is the literature review method. The results of this study indicate that the implementation of learning media based on Animeker in learning is very motivating for students in understanding the subject matter because the Animeker learning media in learning is very varied with video media and animation in each learning media content. Students are very enthusiastic in participating in learning because through Animeker media with various learning videos and animations that vary, students are not bored and learning is not monotonous.